Land capability classification of Vernazza catchment, Cinque Terre National Park, Italy. Issue 2 (9th December 2020) - Scopesi, C.; Olivari, S.; Firpo, M.; Scarpellini, P.; Pini, S.; Rellini, I.
ABSTRACT: Land capability classification is based on chemical and physical properties of soils for agricultural purposes. Objective of this study is the realization of the land capability map in the Vernazza catchment, an historically terraced landscape in the Cinque Terre National Park, recognized as a World Heritage site by UNESCO since 1997. A pedolandscape map with a descriptive legend, based on the soil-landscape paradigm for the prediction of soil classes and their spatial distribution, was produced. After, a land capability map was created by classifying the pedolandscape units to aid the sustainable territorial planning in the National Park. The results were plotted on a 1:4000 scale map with a descriptive legend. Land capability map is dominated by lands with severe limitation and only the 30% of the study area may be used for crops but it requires very careful management and conservation practice.